Report on 3,143.6-km Time and Frequency Transfer Fiber Link with Ps-level Stability - Liu, Bo; Guo, Xinxing; Chen, Jiang; Zhou, Yanli; Liu, Tao; Dong, Ruifang; Zhang, Shougang (Chinese physics letters, 2025)
This letter describes the implementation of a high-precision time and frequency transmission system using a two-way and wavelength division multiplexing scheme over 3,143.6 km of field fiber links, connecting 21 sites between Xi’an and Beijing, China. This scheme incorporates a link noise clean-up system (LNCUS), wherein a controlled very-low-phase noise BVA oscillator acts as an internal frequency source at the relay site to effectively suppress the interference caused by the fiber link noise. Additionally, the high-stability pulse generation technology in the LNCPS provides sufficient short-term stability to significantly improve the stability of the fiber time transfer. The results indicate a time transfer stability in terms of time deviation (TDEV) of less than 2.07 ps@1s, 5.9 ps@100,000s, and combined uncertainty of less than 49.29 ps for the 3,143.6 km field fiber link. The results represent a significant breakthrough in achieving high-accuracy time transfer and continuous operation over ultralong-span field optical fibers exceeding 3,000 km for the first time. This enabled time transfer and synchronization services over the longest international optical fiber distance, thereby establishing a fundamental basis for constructing a nationwide high-precision time service through optical fiber networks.